PS-B07-6: L-ARGININE SUPPLEMENTATION SUBSTANTIALLY ATTENUATES HYPERTENSION BUT NOT CARDIAC INJURY IN RATS WITH METABOLIC SYNDROME. (January 2023) - Tagami, Kaito; Okuzawa, Touko; Hayakawa, Misaki; Cui, Xixi; Obara, Natsuki; Kunimatsu, Asuko; Koide, Mayako; Teranishi, Tamami; Furukawa, Nozomi; Sakabe, Nanako; Ikeda, Katsuhide; Murohara, Toyoaki; et al.
Abstract : Objective: L-arginine is not only a building block for protein but also a physiological substrate for the synthesis of nitric oxide (NO) and plays a regulatory role in signal transduction pathways in cells. Dietary L-arginine supplementation reduced fat mass both in Zucker diabetic fatty rats and in diet-induced obese rats. However, little is known about the effects of L-arginine on cardiac morphology and function in metabolic disorders. We have now examined the effects of L-arginine on cardiac pathology in DahlS.Z-Leprfa/Leprfa (DS/obese) rats, an animal model of metabolic syndrome (MetS). Design and method: DS/obese rats and their homozygous lean (DahlS.Z-Lepr+/Lepr+, or DS/lean) littermate controls were fed a purified control diet and were supplemented with 0.50% L-arginine-HCl or 0.85% L-alanine (isonitrogenous control) in drinking water from 13 to 17 weeks of age. Results: L-arginine supplementation did not affect body weight, visceral and subcutaneous fat mass, insulin resistance, or food and water intake in DS/obese rats, but substantially alleviated hypertension. However, left ventricular (LV) and cardiomyocyte hypertrophy and the upregulation of myocardial fetal-type gene expression, macrophage infiltration in the heart, and increased perivascular and interstitial fibrosis of the LV myocardium and the upregulation of fibrosis-related gene expression were not improved by such intervention. Additionally, L-arginine did not ameliorate impairments of Doppler- or micromanometer-derived indices of LV diastolic function. None of these parameters were influenced by L-arginine supplementation in DS/lean rats. Conclusions: L-arginine supplementation substantially ameliorated hypertension but did not attenuate LV remodeling or diastolic dysfunction in this model of MetS. These data suggest that in addition to its role as a precursor of NO, L-arginine may play a role as a functional amino acid that modulates growth and inflammation.